A review on a hidden gem: Phycoerythrin from blue-green algae - Tan, Hui Teng; Md.Yusoff, Fatimah; Khaw, Yam Sim; Noor Mazli, Nur Amirah Izyan; Nazarudin, Muhammad Farhan; Shaharuddin, Noor Azmi; Katayama, Tomoyo; Ahmad, Siti Aqlima (Multidisciplinary Digital Publishing Institute, 2022)
Phycoerythrin (PE) is a pink/red-colored pigment found in rhodophytes, cryptophytes, and blue-green algae (cyanobacteria). The interest in PE is emerging from its role in delivering health benefits. Unfortunately, the current cyanobacterial-PE (C-PE) knowledge is still in the infant stage. It is essential to acquire a more comprehensive understanding of C-PE. This study aimed to review the C-PE structure, up and downstream processes of C-PE, application of C-PE, and strategies to enhance its stability and market value. In addition, this study also presented a strengths, weaknesses, opportunities, and threats (SWOT) analysis on C-PE. Cyanobacteria appeared to be the more promising PE producers compared to rhodophytes, cryptophytes, and macroalgae. Green/blue light is preferred to accumulate higher PE content in cyanobacteria. Currently, the prominent C-PE extraction method is repeated freezing–thawing. A combination of precipitation and chromatography approaches is proposed to obtain greater purity of C-PE. C-PE has been widely exploited in various fields, such as nutraceuticals, pharmaceuticals, therapeutics, cosmetics, biotechnology, food, and feed, owing to its bioactivities and fluorescent properties. This review provides insight into the state-of-art nature of C-PE and advances a step further in commercializing this prospective pigment.